Integration of Islamic Legal Values and Positive Law in the Peaceful Settlement of Mortgage Right Execution in Indonesia: A Comparative Analysis - Sherhan, Sherhan; Marpaung, Rolando; Mendrofa, Shentice; Purnamasari T, Jelita (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2025)
Ideally, the reconciliation process in the execution of security rights in Indonesia should provide a dispute-resolution mechanism that is not only effective and ensures legal certainty but also grounded in substantive justice, mutual consent, and the protection of public interest as taught in Islamic law. However, in reality, the reconciliation mechanism available in positive law is often treated merely as an administrative procedure and has yet to fully reflect the ethical values of sulh, ibra, and the principles of justice that form the foundation of Islamic law. The integration of Islamic legal values and positive law within the reconciliation process of security-rights execution demonstrates that both legal systems share a similar orientation in achieving peaceful, fair, and substantively just dispute resolution, wherein the normative instruments of positive law and the principles of sulh, ibra, and maslahah in Islamic law complement each other. Comparative analysis affirms that the procedural formalism of positive law and the ethical dimensions of Islamic law can be harmonized to form a more integrative reconciliation model, allowing the execution process to be not only juridically effective but also humanistic, moral, and responsive to the social needs of Indonesian society.